Failure analysis of compressed earth block using numerical plastic damage model - Bouhiyadi Samir; Souinida Laidi; El hassouani Youssef (Fracture and Structural Integrity)
In the last decade, several studies have been introduced to the development and use of compressed earth blocks in green building construction. Studying the evaluation of existing cracks in construction buildings by these blocks is an important industrial and safety subject in recent research. This objective opens a new field in building construction where we describe the mechanical behavior of compressed earth solid blocks. In addition, we offer a solution to rupture damages presented by the propagation of masonry cracks. This paper aims to explore a numerical study using ABAQUS where we analyze the mechanical properties of this block. We started by investigating the elastic phase for this material and it has been generalized to a study in the plastic regime and rupture for the studied block. The different results of simulation shows that macro-cracks generate in the extremities and intersect each other horizontally and/or propagate towards the upper part of the block in a way that is practically parallel to the application of the compression test force